BAHAEDDİN ÖZKİŞİ'NİN ROMANLARININ TEMATİK VE YAPI BAKIMINDAN İNCELENMESİ - YILMAZ, UMAY SELCEN (Fırat Üniveristesi, 2006)
Bahaeddin Özkişi who was born in İstanbul in 1928, to taked part in 20. century Turkısh Literature with his stories and novels; he succeeded to capture to a style special to him with his expression and choosed subjects. The writer, used a comprehensible and net expressions, to loaded impressive meanings to details that we eve neglected usually and he dealed with the events psychologaclly. Bahaeddin Özkişi who grewn with comprehensive Sufism culture, reflected this to his works. So, his works –novels and stories- is like his mirror. Bahaeddin Özkişi is a writer and however he is an artist who signed to different business. He made the models of old İstanbul houses' and he gilded on the glass. KEY WORDS: Novel, Thematre Power, Sufism, Existence, Real, Human

1928'de İstanbul'da dünyaya gelen Bahaeddin Özkişi, hikâye ve romanlarıyla 20. yüzyıl Türk Edebiyatı yazarları arasında yer almış; dili, anlatımı ve seçtiği konularla kendine has bir çizgi yakalamayı başarmıştır. Yazar eserlerinde açık ve net bir dil kullanmış, günlük hayatta çoğu zaman ihmal ettiğimiz ayrıntılara derin anlamlar yüklemiş ve olayları psikolojik yönleri ile ele almıştır. Büyük bir tasavvuf ruhu ve kültürü ile yetişmiş olan Bahaeddin Özkişi bunu eserlerine de yansıtmıştır. Bu bakımdan eserleri yazarın aynası gibidir. Bahaeddin Özkişi, yazar kimliğinin yanında farklı çalışmalara da imza atan bir sanatçıdır. Eski İstanbul evlerinin maketlerini yapmış, cam üzerine tezhip çalışmıştır. ANAHTAR KELİMELER: Roman, Tematik Güç, Tasavvuf, Varlık, Hakikat, İnsan.
Analysis of the novels of Bahaeddin Özkişi in terms of theme and structure
Keywords: Türk Dili ve Edebiyatı